Full-scale experimental study of moisture condensation on the glazing surface: condensation rate characterization. Issue 3 (September 2019) - Nguyen, C K; Teodosiu, C; Kuznik, F; David, D; Rusaouën, G
Abstract: Excessive indoor moisture promotes the growth of mold and condensation on building envelope, which lead to severe IAQ problems. Given the transient, unsteady heat and mass transfer problem, studies dealing with the condensation phenomenon are generally lacking in the literature, especially studies on the condensation rate prediction. Consequently, this paper presents a method to quantify experimentally the condensation rate of droplets formed on a cold glazing surface in a full-scale entirely controlled test room (6.2 x 3.1 x 2.5 m). The condensation qualitative characterization, i.e. the moment of its appearance and its growth mechanism, is achievable using a macro-photography technique. From the time-series of droplet images captured, an image post-processing method is used to detect the droplet contours and to estimate the condensation mass flow rate. Comparisons between experimental and theoretical results show some agreement, which could validate the feasibility of imaging techniques in full-scale condensation studies. Those first results are encouraging and valuable since there were no similar studies in the literature at such the scale. Further investigations are needed in order to clarify all these aspects related to the accuracy of the condensation rate quantification methodology developed in this work.